2019
DOI: 10.1016/j.jpaa.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Non-existence of Hopf–Galois structures and bijective crossed homomorphisms

Abstract: By work of C. Greither and B. Pareigis as well as N. P. Byott, the enumeration of Hopf-Galois structures on a Galois extension of fields with Galois group G may be reduced to that of regular subgroups of Hol(N ) isomorphic to G as N ranges over all groups of order |G|, where Hol(−) denotes the holomorph. In this paper, we shall give a description of such subgroups of Hol(N ) in terms of bijective crossed homomorphisms G −→ N , and then use it to study two questions related to non-existence of Hopf-Galois struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…It remains to consider the groups NG. In [18, Theorem 1.6], the author has shown that if G is the double cover of An with n5, then e(G,N)=0 for all groups NG of order n!. We shall extend this result and prove: Theorem If G is a finite quasisimple group, then e(G,N)=0 for all groups NG of order |G|.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It remains to consider the groups NG. In [18, Theorem 1.6], the author has shown that if G is the double cover of An with n5, then e(G,N)=0 for all groups NG of order n!. We shall extend this result and prove: Theorem If G is a finite quasisimple group, then e(G,N)=0 for all groups NG of order |G|.…”
Section: Introductionmentioning
confidence: 90%
“…Recall that G is said to be quasisimple if G=[G,G] and G/Z(G) is simple, where [G,G] is the commutator subgroup and Z(G) is the center of G. In [18, Theorem 1.3], the author has already shown that: Theorem If G is a finite quasisimple group, then e(G,G)=2.…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, suppose that g is bijective, and we shall prove Proposition 2.1 (b) By Proposition 2.1 (a), the group N is not perfect, so it has a proper and maximal characteristic subgroup M containing [N, N ]. The quotient N/M is then abelian, and by the proof of the second statement of [10,Theorem 1.7], we know that A n = g −1 (M). This means that g restricts to a bijective map res(g) : A n −→ M; res(g)(σ) = g(σ).…”
Section: 2mentioning
confidence: 98%
“…Since M = Z(N ), the map (2.4) is injective, by [10,Proposition 3.5 (c)], for example. It follows that Out(N ) embeds into Out(N/M) ≃ Out(A n ) and so is abelian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation